Involvement of YTHDF1 in renal fibrosis progression via up‐regulating YAP. Issue 2 (6th January 2022) - Xing, Jia; He, Yu‐Chen; Wang, Kai‐Yue; Wan, Peng‐Zhi; Zhai, Xiao‐Yue
Abstract: Renal fibrosis is a progressive, fatal renal disease characterized by the aberrant accumulation of myofibroblasts that produce excess extracellular matrix (ECM) in the renal interstitium and glomeruli. Yes‐associated protein (YAP) has been regarded as a crucial modulator in myofibroblast transformation, but its upstream regulator remains a mystery. In the present study investigating the participation of m6A methylation during renal fibrosis through bioinformatics analysis, we identified YTHDF1, a modulator of m6A methylation, as a key contributor for renal fibrosis because it was highly expressed in human fibrotic kidneys and had a significant correction with YAP. Their co‐localization in human fibrotic kidneys was additionally shown by immunofluorescence. We then found that YTHDF1 was also up‐regulated in fibrotic mouse kidneys induced by unilateral ureteral obstruction (UUO), high‐dose folic acid administration, or the unilateral ischemia‐reperfusion injury, further supporting a causal role of YTHDF1 during renal fibrosis. Consistent with this notion, YTHDF1 knockdown alleviated the progression of renal fibrosis both in cultured cells induced by transforming growth factor‐beta administration and in the UUO mouse model. Meanwhile, YAP was accordingly down‐regulated when YTHDF1 was inhibited. Furthermore, the specific binding of YTHDF1 to YAP mRNA was detected using RNA Binding Protein Immunoprecipitation, and the up‐regulation of fibrotic related molecules in cultured cells induced by YTHDF1 over‐expression plasmid was attenuated by YAP siRNA. Taken together, our data highlight the potential utility of YTHDF1 as an indicator for renal fibrosis and suggest that YTHDF1 inhibition might be a promising therapeutic strategy to alleviate renal fibrosis via downregulating YAP.